Empowerment of Coastal Communities of Lakkang Island, Tallo District, Makassar City - Yamin, Muh Nur; Ruslan, Muh Reza Hidayat; Ismail, Ismail; Johansyah, Oky Nur Pratiwi (Jurnal Aktor, 2024)
This study aims to determine the Empowerment of Coastal Communities in Lakkang Island Tallo District Makassar City and the supporting and inhibiting factors for Empowering Coastal Communities in Lakkang Island, Tallo District, Makassar City. This study uses a qualitative approach. Data collection is done through observation techniques, interviews, and documentation. The data analysis technique used in this study is interactive data analysis through the stages: data condensation, data presentation, and conclusion testing.The results of this study indicate that the empowerment of coastal communities has been carried out and in accordance with the existing implementation stages and standards. This can be seen from several programs, namely socialization by the provincial and district governments initiated by the village government to improve the welfare of coastal communities. The impact of empowerment on community independence aims to build the independence of coastal communities on Lakkang Island and reduce community dependence on the government. As for the supporting factors in empowering the coastal communities of Langkakan Island, namely the concept of awareness has been built in carrying out all kinds of activities in accordance with existing laws. The inhibiting factors for the empowerment of the coastal community on Lakkang Island, Tallo sub-district, Makassar City, include limited capital, natural factors, facilities and infrastructure, lack of enthusiasm for tourism, lack of regular income, and lack of knowledge about the use of facilities.